2016
DOI: 10.1364/ao.55.006156
|View full text |Cite
|
Sign up to set email alerts
|

Performance of low-cost few-mode fiber Bragg grating sensor systems: polarization sensitivity and linearity of temperature and strain response

Abstract: We evaluate whether 850 nm fiber Bragg grating (FBG) sensor systems can use low-cost 1550 nm telecom fibers; in other words, how detrimental the influence of higher-order modes is to the polarization stability and linearity of the strain and temperature response. We do this by comparing polarization sensitivity of a few-mode 850 nm FBG sensor to a strictly single-mode 850 nm FBG sensor system using 850 nm single-mode fibers. We also compare the performance of the FBGs in strain and temperature tests. Our resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The resolution of the optical signal demodulation equipment is 1 pm, the sampling frequency is 2 kHz, and the wavelength demodulation range matches the ASE broadband light source. In the experiment, a temperature and humidity programmable chamber (Temp-Humi PC) is used to provide temperature jumps, the controllable temperature range is −30 • C∼120 • C, and the accuracy is 0.01 • C, which meets the requirements of the experimental system [3,11]. In the experiment, the broadband light output by the ASE is injected into the FBG temperature sensor through the circulator, the temperature sensor grating returns the light signal of a specific wavelength, and the reflected light enters the demodulation device through the circulator.…”
Section: Experiments Of Fbg Temperature Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The resolution of the optical signal demodulation equipment is 1 pm, the sampling frequency is 2 kHz, and the wavelength demodulation range matches the ASE broadband light source. In the experiment, a temperature and humidity programmable chamber (Temp-Humi PC) is used to provide temperature jumps, the controllable temperature range is −30 • C∼120 • C, and the accuracy is 0.01 • C, which meets the requirements of the experimental system [3,11]. In the experiment, the broadband light output by the ASE is injected into the FBG temperature sensor through the circulator, the temperature sensor grating returns the light signal of a specific wavelength, and the reflected light enters the demodulation device through the circulator.…”
Section: Experiments Of Fbg Temperature Sensitivitymentioning
confidence: 99%
“…The wavelength drift of the fiber Bragg grating (FBG) reflection spectrum is directly related to temperature changes, so the FBG temperature sensor is one of the most important and direct application directions of fiber-grating-sensing technology [1]. FBG temperature sensors are used in many applications, such as strong magnetic fields, electric power plants, etc., due to the advantages of antielectromagnetic interference, wide dynamic range, strong reliability, and fast response performance [2,3]. Most commonly, the FBG temperature sensor is buried in the concrete to track the groundwater temperature field of ultra-high hydropower dams, and buried in the rock layer soil to monitor the frost heaving environment of the soil in the alpine tunnel and slope.…”
Section: Introductionmentioning
confidence: 99%
“…Optical fiber sensors based on Raman scattering [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ], Brillouin [ 16 , 17 ], and fiber Bragg grating [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] are three common ways to realize multipoint measurement. Rusen Yan et al [ 9 ] reported a temperature-dependent Raman sensor, and the temperature sensitivities are −0.011 cm −1 /K and −0.013 cm −1 /K for different modes in the range from 100 K to 320 K, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Stefani and Anziy introduced the few-mode 850 nm FBG sensor [ 8 , 28 ]. The characteristics of this FBG, such as polarization stability and linearity, were provided in their articles.…”
Section: Introductionmentioning
confidence: 99%